2017
DOI: 10.1371/journal.pone.0174667
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted high throughput sequencing in hereditary ataxia and spastic paraplegia

Abstract: Hereditary ataxia and spastic paraplegia are heterogeneous monogenic neurodegenerative disorders. To date, a large number of individuals with such disorders remain undiagnosed. Here, we have assessed molecular diagnosis by gene panel sequencing in 105 early and late-onset hereditary ataxia and spastic paraplegia probands, in whom extensive previous investigations had failed to identify the genetic cause of disease. Pathogenic and likely-pathogenic variants were identified in 20 probands (19%) and variants of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 45 publications
(43 reference statements)
1
39
2
Order By: Relevance
“…This same variant was also observed in a multigeneration Sicilian family with a more variable phenotype, complicated in some members by psychomotor delay, hand amyotrophy, and sensory abnormalities 12. Finally, Iqbal et al 13. found that both c.80T>C, p.Ile27Thr and c.22G>A, p.Val8Met were associated with pure HSP in multigeneration families.…”
Section: Introductionmentioning
confidence: 65%
“…This same variant was also observed in a multigeneration Sicilian family with a more variable phenotype, complicated in some members by psychomotor delay, hand amyotrophy, and sensory abnormalities 12. Finally, Iqbal et al 13. found that both c.80T>C, p.Ile27Thr and c.22G>A, p.Val8Met were associated with pure HSP in multigeneration families.…”
Section: Introductionmentioning
confidence: 65%
“…Many disease-associated mutations have been found in the motor domain of KIF1A (24,26,27). We noticed that the gain-of-function V6I mutation in unc-104, identified in our C. elegans genetic screen, is equivalent to the dominant SPG-associated mutation, V8M, in human KIF1A (12,27) (Figs 1A and B). Our previous data revealed that worm UNC-104(V6I) and mouse KIF1A(V8I) are constitutive active in worm neurons and COS-7 cells, respectively (12).…”
Section: Not All Disease-associated Mutations In Kif1a Are Loss-of-fumentioning
confidence: 77%
“…Many mutations in the motor domain of KIF1A are associated with neuronal diseases, leading to both the pure and complicated forms of SPG, as well as mental retardation (24,26,27). However, it remained unknown why different mutations cause different types of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using NGS in disease-specific contexts have reported high diagnostic yields ranging from 19% for spastic paraplegia to 60% for neuromuscular disorders. [9][10][11] Historically, copy number variant (CNV) analysis has been limited to only a narrow group of genes 12 or has not been routinely performed in neuromuscular genetic testing. 9,13,14 Recently, the accurate detection of CNVs alongside sequence variants by NGS in a single assay has enabled more comprehensive, more affordable, and faster genetic analysis with a single sample.…”
mentioning
confidence: 99%